Method of fast construction of M-sequence feedback functions with polynomial representation - Jie GUAN; Congwei ZHOU (Tongxin xuebao)
The construction of M-sequence feedback functions has always been a hotspot in the theory of stream cipher.Based on the structural properties of the M-sequence feedback function constructed by the m-sequence,the method of fast construction of a class M-sequence feedback functions was proposed by combining the function transformation and function derivative.Meanwhile,polynomial representation,amount and weight property of the class M-sequence feedback functions were considered.